2003
DOI: 10.1074/jbc.m306083200
|View full text |Cite
|
Sign up to set email alerts
|

β-Synuclein Displays an Antiapoptotic p53-dependent Phenotype and Protects Neurons from 6-Hydroxydopamine-induced Caspase 3 Activation

Abstract: We have established stable transfectants expressing ␤-synuclein in TSM1 neurons. We show that in basal and staurosporine-induced conditions the number of terminal deoxynucleotidyltransferase-mediated dUTP nick end-labeling (TUNEL)-positive ␤-synuclein-expressing neurons was drastically lower than in mock-transfected TSM1 cells. This was accompanied by a lower DNA fragmentation as evidenced by the reduction of propidium iodide incorporation measured by fluorescence-activated cell sorter analysis. ␤-Synuclein st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
79
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 50 publications
(34 reference statements)
3
79
0
Order By: Relevance
“…Thus, both synphilin-1 and ␤-synuclein remain protective toward 6OH-DOPA (55) and lower the p53 pathway. Furthermore, ␤-synuclein restores the protective activity of ␣-synuclein, even in the presence of 6OH-DOPA (55). Whether synphilin-1 restores the antiapoptotic potential of ␣-synuclein in the presence of the dopaminergic derivative remains to be established.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, both synphilin-1 and ␤-synuclein remain protective toward 6OH-DOPA (55) and lower the p53 pathway. Furthermore, ␤-synuclein restores the protective activity of ␣-synuclein, even in the presence of 6OH-DOPA (55). Whether synphilin-1 restores the antiapoptotic potential of ␣-synuclein in the presence of the dopaminergic derivative remains to be established.…”
Section: Discussionmentioning
confidence: 97%
“…It should be noted that this type of regulation has already been documented for other proteins. Thus, presenilins (54,55) and ␤-amyloid precursor protein (56 -60) undergo caspase-derived cleavages, generating proteolytic fragments controlling cell death. More related to PD, parkin, another binding partner of synphilin-1 (18,61) displaying an antiapoptotic phenotype (62,63), is also cleaved by caspases, but unlike for synphilin-1, this endoproteolysis leads to a loss of function of this protein (64).…”
Section: Discussionmentioning
confidence: 99%
“…30 The mechanisms of neuroprotection appear to be independent of upstream effects such as phosphatidylinositol 3-kinase (PI3-K) and phosphoinositide-dependent kinase (PDK)-1 and involve direct binding of b-synuclein to Akt, resulting in increased stability of the kinase and phosphorylation of downstream signaling molecules such as glycogen synthase kinase 3b (GSK3b) 30 and p53. 41 In regard to the latter signaling pathway, a recent study showed that b-synuclein protects from the toxic effects of 6-hydroxydopamine by decreasing the expression of the proapoptotic gene p53. 41 The mechanisms linking the effects of b-synuclein to the Akt and p53 signaling pathways are not completely clear.…”
Section: Discussionmentioning
confidence: 99%
“…41 In regard to the latter signaling pathway, a recent study showed that b-synuclein protects from the toxic effects of 6-hydroxydopamine by decreasing the expression of the proapoptotic gene p53. 41 The mechanisms linking the effects of b-synuclein to the Akt and p53 signaling pathways are not completely clear. However, recent studies have shown that p53 expression and activity are regulated by Mdm2, 42 an oncoprotein that under normal conditions is restricted to the cytoplasm but when phosphorylated by activated Akt is translocated to the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…·-, ß-, and Á-synuclein differ considerably in their acidic C-terminal domains, which is presumably where their functional differences arise, while share a characteristically conserved N-terminal domain, which arises presumably similar biological effects such as the chaperone activity and reversible binding to phospholipid membranes (4). All of these suggest that the relationship between ·-, ß-, and Á-synuclein may be restriction or complementation, for instance, ·-synuclein is the major pathological component of Parkinson's disease and Alzheimer's disease, and ß-, and Á-synuclein levels could reflect a neuroprotective role to inhibit the aggregation of ·-synuclein proteins (7,8,(28)(29)(30). On the other hand, the following situation might exist.…”
Section: -------------------------------------------------mentioning
confidence: 99%